The Implementation of Quizzi AI as a Learning Tool on Learning Outcomes in Islamic Religious Education in Year 12 at SMAIT Harapan Bunda, Semarang - Baen, Faldin; Habibah, Mu’minatul; Mujtaba, Hamid; Fairuzzuhria, Novie (Dirasah: Jurnal Pendidikan Islam, 2026)
This study aims to examine the application of Quizzi AI as a pedagogical tool designed to improve educational outcomes in Islamic Religious Education (PAI) among Year 11 students at SMAIT Harapan Bunda, Semarang. The research employed a quantitative methodology using a quasi-experimental framework, incorporating pre-test and post-test assessments administered to 64 participants categorised into two instructional modalities: traditional learning and Quizzi AI-enhanced learning. The research instruments comprised an academic performance assessment and an observational tool designed to evaluate students’ motivation and engagement during the PAI instructional process. The findings revealed a significant improvement in average student performance, rising from 64.2 in the pre-tests to 89 in the post-tests following the integration of Quizzi AI into the educational experience. This increase is further evidenced by a rise in the percentage of academic adherence, alongside heightened enthusiasm and active participation among students during educational activities. Consequently, the application of Quizzi AI demonstrates its effectiveness as an interactive educational tool capable of optimising PAI learning outcomes at secondary education level. The implications of this study indicate that the application of Quizzi AI not only improves student learning outcomes in Islamic Religious Education subjects but can also serve as an interactive learning model that fosters active student participation, motivation, and enthusiasm. This provides a foundation for educators to integrate gamification-based educational technologies into the curriculum, thereby enhancing the effectiveness of learning at secondary school level.